Humic-like acids from hydrochars: Study of the metal complexation properties compared with humic acids from anthropogenic soils using PARAFAC and time-resolved fluorescence - Santos, Joao Vitor dos [UNESP] (2020)
Humic acids (HA) play an important role in the distribution, toxicity, and bioavailability of metals in the environment. Humic-like acids (HLA) that simulate geochemical processes can be prepared by NaOH aqueous extraction from hydrochars produced by hydrothermal carbonization (HTC). HLA can exhibit properties such as those found in HA from soils, which are known for their ability to interact with inorganic and organic compounds. The molecular characteristics of HLA and HA help to explain the relationship between their molecular features and their interaction with metallic species. The aim of this study is to assess the molecular features of HA extracted from Terra Mulata (TM) and HLA from hydrochars as well as their interaction with metals by using Cu(II) ions as a model. The results from C-13 NMR, elemental analysis, FTIR, and UV-Vis showed that HA are composed mostly of aromatic structures and oxygenated functional groups, whereas HLA showed a mutual contribution of aromatic and aliphatic structures as main constituents. The interactions of HA and HLA with Cu(II) ions were evaluated through fluorescence quenching, in which the density of complexing sites per gram of carbon for interaction was higher for HLA than for HA. Furthermore, the HLA showed similar values for stability constants, and higher than those found for other types of HA in the literature. In addition, the average lifetime in both humic extracts appeared to be independent of the copper addition, indicating that the main mechanism of interaction was static quenching with a non-fluorescent ground-state complex formation. Therefore, the HLA showed the ability to interact with Cu(II) ions, which suggests that their application can provide a new approach for remediation of contaminated areas. (C) 2020 Elsevier B.V. All rights reserved.